STATUS KERBAU MOA BERDASARKAN STRUKTUR POPULASI DAN LAJU SILANG DALAM PER GENERASI - Riri Sarfan; Rajab Rajab (JURNAL HUTAN PULAU-PULAU KECIL, 2023)
This study aims to determine the population structure and cross-rate per generation of Moa buffalo on Moa Island as a source of information about the status of the buffalo population. The survey was conducted on 60 respondent breeders who raise buffalo in three sample village locations, and data collection was conducted by conducting interviews with buffalo breeders and direct observation in the field. The variables observed included population structure, actual population, effective population and cross-over rate per generation. The results showed that the composition of Moa buffalo from the total population was male 5.45% : female child 4.55% (1.2 : 1), young male 11.27% : young female 10.18% (1.11 : 1) ), and adult males 18.91% : adult females 49.64% (1 : 2.63); (2) The actual population size of Moa buffalo is 377 heads, with an effective population size of 301 heads; (3) the rate of inbreeding per generation of Moa buffalo is 0.16%. Indicates that there is no pressure on buffalo population.